Learning from Literature and Heritage - Aleksandar Staničić; Angeliki Sioli (Footprint)
This editorial is an introduction to the issue of Footprint 34, ‘Narrating Shared Futures’. The issue is dedicated to a transdisciplinary encounter between literature and cultural heritage, namely, here we seek to understand how literature can help us unpack complex meanings of places of heritage, and use that knowledge to imagine, design and produce shared and inclusive futures. We elaborate on three notions that appear in the title of the issue – ‘narrating’, ‘shared’ and ‘futures’ – and then we explain how each of the articles featured in this volume contributes to the proposed framing. We conclude with a brief discussion of ways in which the past, present and future are constantly being made in-the-now through both literary and design techniques.